The Influence of Career Development and Rewards on Campus Employee Performance at STIE Professional Management College Indonesia - Niastyna Simorangkir; Pius Deski Manalu (International Journal of Management Research and Economics, 2024)
Lack of employee productivity can hinder the performance and goals of an organization. The aim of this research is to investigate the influence of career development, giving rewards, on employee performance at the STIE PMCI Campus. This research uses a quantitative approach involving 30 respondents as population and sample. The research results show that the independent variable career development (X1) is obtained t - count (5,230) > t -table (2.052), the Reward variable (X2) with t - count (2,833) > t- table (2.052), then the career development variable (X1) has a partial effect on the employee performance variable (Y), and the reward variable (X2) has a partial effect on the employee performance variable. The results of the F test show that f-count (15, 228 ) > f- table (2.98), while the significance is 0.000 < alpha at a significant level of 0.05, so Ho is rejected and Ha is accepted, which means the independent variable (career development, reward) together or simultaneously influence the dependent variable (employee performance) positively and significantly. It is recommended that the STIE PMCI leadership be able to improve the performance of their employees by opening up opportunities for career development, providing awards on an ongoing basis and always motivating their employees.